2022
DOI: 10.3390/ijms232113564
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Potential of Plants against COVID-19 during Outbreaks—An Update

Abstract: Several human diseases are caused by viruses, including cancer, Type I diabetes, Alzheimer’s disease, and hepatocellular carcinoma. In the past, people have suffered greatly from viral diseases such as polio, mumps, measles, dengue fever, SARS, MERS, AIDS, chikungunya fever, encephalitis, and influenza. Recently, COVID-19 has become a pandemic in most parts of the world. Although vaccines are available to fight the infection, their safety and clinical trial data are still questionable. Social distancing, isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 159 publications
0
8
0
1
Order By: Relevance
“…Plant extracts and plant-derived secondary metabolites have broad-spectrum antimicrobial activity and can exhibit properties against SARS-CoV-2 replication [ 5 , 39 , 40 , 41 ]. Here, chemometric analyses suggest that myrtucommulones, more prevalent in the multitarget species E. mosenii and E. prasina , may be the main contributor to the strong inhibitory virus effect exhibited by these extracts.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Plant extracts and plant-derived secondary metabolites have broad-spectrum antimicrobial activity and can exhibit properties against SARS-CoV-2 replication [ 5 , 39 , 40 , 41 ]. Here, chemometric analyses suggest that myrtucommulones, more prevalent in the multitarget species E. mosenii and E. prasina , may be the main contributor to the strong inhibitory virus effect exhibited by these extracts.…”
Section: Resultsmentioning
confidence: 99%
“…Molecular docking analyses revealed that the bioactive compound gingerol, extracted from Zingiber officinale (Zingiberaceae family), prevents the entry and fusion of coronavirus by blocking the TMPRSS2 receptor [43,44]. Flavonoids such as kaempferol, luteolin, sulforaphane, quercetin, and cryptotanshinone, found in different plant families, also exhibit inhibitory Plant extracts and plant-derived secondary metabolites have broad-spectrum antimicrobial activity and can exhibit properties against SARS-CoV-2 replication [5,[39][40][41]. Here, chemometric analyses suggest that myrtucommulones, more prevalent in the multitarget species E. mosenii and E. prasina, may be the main contributor to the strong inhibitory virus effect exhibited by these extracts.…”
Section: Myrtaceae Extracts Inhibit Sars-cov-2 Replication In Infecte...mentioning
confidence: 99%
“…El distanciamiento físico obligatorio, la higiene de manos y, posiblemente, el uso adecuado de equipo de protección personal, incluido el uso de una mascarilla quirúrgica, siguen siendo la forma más efectiva de controlar la propagación de la enfermedad, y la mayoría de los países que adoptaron tales medidas informaron cierto éxito en frenar la propagación de la enfermedad [18][19][20][21]. Actualmente existe un tratamiento o vacuna no confiable disponible para combatir el SARS-CoV-2 [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39].…”
Section: Introductionunclassified
“…The usability of NAIs may largely depend on the metabolic activation, and they also compete with the intracellular pool of natural nucleoside triphosphates (NTPs). Nonnucleotide analogue inhibitors (NNAIs) do not face these challenges as they bind to both active but also allosteric sites of the RdRp, and therefore they represent a promising NAI alternative [ 12 ].…”
Section: Introductionmentioning
confidence: 99%